(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: Chronic diseases and non-communicable diseases constitute a relevant public health problem in Brazil and in the world. Objectives: To describe the actions developed to build the Surveillance of Non-Communicable Diseases and Disorders (NCDs) in public health in Espírito Santo, highlighting the published works and events developed in the present State. Methods: This is a narrative review of institutional initiatives and publications produced, covering the chronology of events and schedules developed by the NCD Surveillance Technical Team in the Strategic Health Surveillance Management. Results: The initiatives promoted for the construction of NCD Surveillance, according to the chronology of publications, comprised 10 Epidemiological Bulletins, 3 Epidemiological Notebooks and 1 Cancer Surveillance Newsletter, published in the period 2001-2017. Regarding the initiatives of institutional events, 6 State Seminars on NCD Surveillance were identified. Conclusion: The set of actions developed allowed the dissemination of the magnitude of NCDs on the morbimortality framework in Espírito Santo, contributing to theoretical foundations and advocacy, inserting the theme in initiatives such as the State Health Plan (2009) and the Regionalization Master Plan (2011), culminating in the successful preparation of the Strategic Action Plan to Combat Chronic Diseases and Non-Communicable Diseases in the state of Espírito Santo (2017).